W.O.W Enterprise - Azmi, Nurul Azieah; Abd Latiff, Ashsyahira Nasha; Wagimin, Fahifah; Mat Jani, Nur Baizurah; Agandap, Nicole Andrew (2015)
We are the one of business that produces coconut smoothies' product after The Royal Coconut introduces this coconut product to us. Our business was located at Jalan Tanjung Lipat, 88450 Kota Kinabalu, Sabah, Malaysia and we have open one branch at Ground Floor Sulaman Sentral Off Jalan Sepangar Bay, Kuala Menggatal, 88450 Kota Kinabalu, Sabah. This is because the area is proximity to our product resources, proximity to the facilities, low cost rent and strategies place to sell our coconut smoothies product to the customer. Our business opportunity begins with the existence of various customers need and wants for our products. As society becomes more affluent, there will be more human needs and wants to be fulfilled. Our product is something that possesses a physical form that is required to fulfill human wants directly and indirectly. From our view, we believe that this business has potential to be developed accordance to the advantages:-